Comparative dynamic characteristics of electrospun ultrathin fibers and films based on poly(3-hydroxybutyrate) - Staroverova, Olga; Karpova, Svetlana; Iordanskii, Alexey; Olkhov, Anatoliy; Khvatov, Anatoliy; Grumezescu, Alexandru Mihai; Kildeeva, Natalia; Artsis, Marina; Zaikov, Gennady (Publishing House of Lviv Polytechnic National University, 2016)
The dynamic of polymer chains for electrospun poly(3-hydroxybutyrate) (PHB) fibers and the PHB films was studied with spin probe characteristics obtained by ESR technique. The ESR data combined with DSC analysis reveal the presence of two TEMPO probe populations with different correlation times indicating the heterogeneous structure of intercrystalline areas in the films, fibers and the cold rolled fiber mats. The ESR data are in agreement with the 2-mode model of amorphous state in semicrystalline polymers. The difference in peak intensities shows that effective correlation time in the electrospun fibers exceeds the same characteristic in the film, that also indicates the slower molecular mobility in the low-dense amorphous fraction of PHB fibers as compared to the film. The impact of potential aggressive factors such as water, temperature and ozone upon probe mobility allows suggesting that both the fiber electrospinning and the cold-rolling procedure lead to rearrangement in the intercrystalline fields of PHB that contribute to the progress in the fiber stabilization against the aggressive factors. З метою дослідження динаміки полімерних сегментів методом зондової спектроскопії ЕПР проведено порівняльний аналіз плівок та ультратонких волокон полі(3-гідроксибутирату) (ПГБ). Волокна отримані методом електроформування і додатково досліджені методом ДСК. Показано, що у міжкристалічних областях існують дві популяції молекулярного зонду ТЕМПО, які відрізняються часом кореляції і розташовані у більш або менш щільних областях ПГБ, що узгоджується з бімодальною моделлю аморфного стану в частково кристалічних полімерах. Різниця в ЕПР спектрах доводить, що молекулярна рухомість зонду у волокнах сповільнена порівняно з його рухомістю у плівках ПГБ. Додатково розглянутий вплив агресивного середовища (води і озону) за підвищених температур і показано, що в процесах холодної обкатки або витягуванні волокна при електроформуванні відбувається перебудова міжкристалічних областей ПГБ, що сприяє стабілізації фібрилярної структури проти дії зовнішнього агресивного середовища.
Порівняльні динамічні характеристики ультратонких волокон, отриманих електроформуванням і плівок на основі полі(3-гідроксибутирату)
Keywords: poly(3-hydroxybutyrate); electrospinning; ultrathin fibers; film; ESR; TEMPO; chain dynamics; aggressive media; полі(3-гідроксибутират); елекроформування; ультратонкі волокна; плівка; ЕПР; зонд ТЕМПО; динаміка ланцюга; агресивне середовище